Two-dimensional silver nanodot array fabricated using nanoporous alumina for a chemical sensor platform of localized surface plasmon resonance - Jung, M.; Kim, T. -R.; Choi, Y. -W.; Lee, S.; Woo, D.; Ji, M. -G. (ADVANCED FABRICATION TECHNOLOGIES FOR MICRO/NANO OPTICS AND PHOTONICS IX, 2016)
The noble metal nanostructure has attracted significant attention because of their potential applications as sensitive sensor platform blocks for biological and chemical sensing. The unique optical property of the metal nanostructure is originated from localized surface plasmon resonance (LSPR). The fabrication of metal nanostructure is a key issue for sensor applications of LSPR. In this paper, fabrication technique of two-dimensional Ag nanodot array on an indium tin oxide (ITO) glass substrate via the nanoporous alumina mask and the utilization as a platform for LSPR chemical sensor was studied. Well-ordered Ag nanodot array with approximately 65 nm diameter in periodic pattern of 105 nm was fabricated using the nanoporous alumina with through-holes as an evaporation mask. The LSPR of Ag nanodot array on ITO glass substrate was investigated by UV-vis spectroscopy. The LSPR wavelength-shifts owing to the concentration variances of Methylene Blue (MB) adsorbed on Ag nanodot arrays were examined for application of chemical sensor.